Producción, comercialización y rentabilidad de la caña de azúcar (saccharum officinarum) en el recinto Tres Postes, Cantón Baquerizo Moreno de la Provincia del Guayas. - Mendoza Aspiazu, Doris Steffy (2016)
The current research work was aimed at determining the production, commercialization and profitability in which sugarcane producers (Saccharum Officinarum) are involved in the Tres Postes precinct, Baquerizo Moreno canton, province of Guayas; Taking into account the production system and the costs, with the intention of analyzing if the production of sugar cane has an acceptable level of profitability for the cane grower. Using the inductive and analytical methods with descriptive and applied research, using primary and secondary sources. For this, personalized surveys were applied to eighteen sugarcane farmers in the Tres Postes enclosure. Obtaining the necessary information to be able to carry out the stated objectives, this investigation or data were tabulated and confronted of percentage form. The tabulated information indicated that the way to grow sugarcane is in pieces of 80 cm interlaced, the stem used should be between 7 and 8 months of the previous harvest of a crop that has been healthy. Fertilizing the crop is with Urea, complete fertilizer 8-20-20 and muriate, fertilization is done twice a year at the cut and after two months because this crop absorbs nutrients until two months of growth. The price per metric ton is determined by the Ingenio, and this depends on where they sell the crop, and the way to market the sugar cane is direct with the mill there is no intermediary. As an indicator of profitability, the profit / cost ratio was 1.21 for the first year of production, with profitability of 21%; this profitability is achieved with 105 metric tons of production per hectare.